Building performance assessment in terms of energy consumption using building information modeling - Shoubi, Mojtaba Valinejad (2013)
Due to concerning about rising the cost of energy and growing the environmental concerns, the intensive of using sustainable building with minimal environmental impact is increasing worldwide. Our environment is an important aspect, not only for use, but also to conserve. The main objective of this study is to assess the capability of utilizing Building Information Modeling (BIM) to model for building energy performance improvement. The amount of energy consumption of double storey house at Skudai Malaysia is evaluated through Revit and Ecotect software. The study evaluated the annual life cycle performance of the building in terms of cooling energy consumption in operational stage. It also intended to assess different alternative design configurations to identify which design configuration has more impacts on building performance which can reduce embodied energy and lead to energy efficient building. It has been concluded from the study that some materials such as double brick and reverse brick veneer, timber, concrete floor- tiles, plaster insulation and glass sliding in components of wall, windows, floor, ceiling and door respectively are more energy efficient compared to the other materials investigated, and would have beneficial role in reducing the building’s operational embodied energy.